Recreational Snow-Sports Injury Risk Factors and Countermeasures: A Meta-Analysis Review and Haddon Matrix Evaluation - Hume, P; Lorimer, AV; Griffiths, PC; Carlson, I; Lamont, M (Springer International Publishing, 2015)
Background: Snow sports (alpine skiing/snowboarding) would benefit from easily implemented and cost-effective injury prevention countermeasures that are effective in reducing injury rate and severity. Objective: For snow sports, to identify risk factors and to quantify evidence for effectiveness of injury prevention countermeasures. Methods: Searches of electronic literature databases to February 2014 identified 98 articles focused on snow sports that met the inclusion criteria and were subsequently reviewed. Pooled odds ratios (ORs) with 90 % confidence intervals (CIs) and inferences (percentage likelihood of benefit/harm) were calculated using data from 55 studies using a spreadsheet for combining independent groups with a weighting factor based on quality rating scores for effects. Results: More experienced skiers and snowboarders are more likely to sustain an injury as a result of jumps, while beginners sustain injuries primarily as a result of falls. Key risk factors that countermeasure interventions should focus on include, beginner skiers (OR 2.72; 90 % CI 2.15–3.44, 99 % most likely harmful), beginner snowboarders (OR 2.66; 90 % CI 2.08–3.40, 99 % harmful), skiers/snowboarders who rent snow equipment (OR 2.58; 90 % CI 1.98–3.37, 99 % harmful) and poor visibility due to inclement weather (OR 2.69; 90 % CI 1.43–5.07, 97 % harmful). Effective countermeasures include helmets for skiers/snowboarders to prevent head injuries (OR 0.58; 90 % CI 0.51–0.66, 99 % most likely beneficial), and wrist guards for snowboarders to prevent wrist injuries (OR 0.33; 90 % CI 0.23–0.47, 99 % beneficial). Discussion: The review identified key risk factors for snow-sport injuries and evaluated the evidence for the effectiveness of existing injury prevention countermeasures in recreational (general public use of slopes, not racing) snow sports using a Haddon’s matrix conceptual framework for injury causation (host/snow-sport participant, agent/mechanism and environment/community). Conclusion: Best evidence for the effectiveness of injury prevention countermeasures in recreational snow sports was for the use of helmets and wrist guards and to address low visibility issues via weather reports and signage.